Terapi Senam Hipertensi Untuk Menurunkan Tekanan Darah Tinggi Pada Lansia di Puskesmas Wonosalam II Demak - Abrori Abrori; Vina Widaad (Journal of Health, Medical, and Psychological Studies, 2026)
Exercise therapy for hypertension to lower high blood pressure in the elderly consists of movements designed to improve blood flow and oxygen supply, particularly to increase oxygen delivery to the myocardium, thereby lowering blood pressure. This study employed a quantitative, quasi-experimental design with a one-group pre-test and post-test without a control group; that is, there was no comparison (control) group. However, the researcher observed the sample before the hypertension exercise and then observed them again after the exercise. The sample consisted of 97 participants selected via total sampling; data were analyzed statistically using the Wilcoxon test. Before the hypertension exercise intervention, the average systolic blood pressure among the elderly was 163.97 mmHg and the diastolic blood pressure was 100.22 mmHg. The average systolic blood pressure after the intervention was 142.79 mmHg and the diastolic blood pressure was 91.41 mmHg. The Wilcoxon test yielded a p-value of 0.000 (<0.05) for both systolic and diastolic blood pressure. Thus, it can be statistically proven that hypertension exercise is effective as a non-pharmacological therapy for lowering blood pressure in the elderly.